Prevalence of Neisseria meningitidis carriage: a small-scale survey in Istanbul, Turkey - GÜNEŞER, DENİZ; KEPENEKLİ KADAYİFCİ, EDA; BORAN, PERRAN (J INFECTION DEVELOPING COUNTRIES, 2016)
Introduction: The human nasopharynx is the main reservoir of Neisseria meningitidis, and asymptomatic carriage is common. N. meningitidis one of the common causes of bacterial meningitis in Turkey, especially after the implementation of the national immunization program that includes conjugated pneumococcal and Haemophilus influenzae type b vaccines. The purpose of this study was to evaluate the prevalence of meningococcal carriage and determine the leading serogroup, which may help authorities to adapt appropriate meningococal vaccine into the national immunization programme. Methodology: The prevalence of oropharyngeal carriage of N. meningitidis in 1,000 healthy subjects, 0-79 years of age, was investigated. Oropharyngeal swabs were collected during an 18-month period. Samples obtained were inoculated onto Thayer-Martin agar. The API-NH test and VITEK-MS system were used for identification of colonies. Multiplex real-time polymerase chain reaction assay was used to determine serogroups with serogroup-specific genes. Results: N. meningitidis was isolated from 6 of 1,000 subjects (0.6%). Meningoccocal carriers were between 21 and 40 years of age. All isolates were serogrouped as B, except one that did not survive on subculture. N. lactamica was isolated from 13 of 1,000 subjects (1.3%). Conclusions: Carriage rate of meningococci in our study was relatively low. However, we detected that serogroup B was the leading strain in meningococcal carriage in Istanbul; choosing an appropriate meningococcal vaccine containing serogroup B should therefore be considered. High absolute humidity throughout the year in Istanbul may explain the low prevalence of carriage in our study. This should be verified with a multicenter national survey.
Keywords: Neisseria meningitidis; meningococcal carriage; oropharyngeal carriage; healthy subjects; Istanbul; Turkey; BACTERIAL-MENINGITIS; MENINGOCOCCAL MENINGITIS; DISEASE; CHILDREN